The Effect of Earnings Management, Financial Performance and Thin Capitalization on Tax Aggressivity - Setianingsih, Ari; Nursyirwan, Vivi Iswanti (Universitas Pamulang, 2022)
This study aims to discover and test the effects of earning management, financial performance (profitability), and thin capitalization on tax aggressiveness. This research employs an associative quantitative approach with secondary data. This study's population consists of all 8 companies listed on the Indonesia Stock Exchange (IDX) in the category of manufacturing companies in the food and beverage sector from 2017 to 2021. Purposive sampling was used in this study, multiple linear regression methods were used for data analysis, and the data was processed using Eviews version 9. According to the findings of this study, earnings management has an impact on tax aggressiveness, financial performance has no impact on tax aggressiveness, and thin capitalization has no impact on tax aggressiveness. Earning management, financial performance, and thin capitalization simultaneously impact tax aggressiveness.